ADAPTASI KOMUNIKASI ANTARBUDAYA DALAM MENGHADAPI CULTURE SHOCK: (Studi Kasus Mahasiswa Perantau Asal Solo yang Tergabung dalam Komunitas Solo Pride di Universitas Jember) - Rizky Puteri Santoso, Salsabilla Natasya; Riyanto, Buddy; Mahar Rizqi, Fikriana (Solidaritas, 2024)
Abstract Social interaction an important part of human life, making the ability to adapt very necessary, especially when in a new environment. Students from Solo who are members of the Solo Pride Community who choose to continue their studies at the University of Jember campus experience obstacles when adapting due to differences in cultural backgrounds such as language, social norms and cultural values which can hinder the communication process and trigger culture shock to overcome these obstacles, Solo students carried out an adaptation process. This research aims to find out the adaptation process carried out by Solo students in facing culture shock in the city of Jember. The method used in this research is descriptive qualitative. Data was obtained from interviews and observations with informants, namely students from Solo who are members of the Solo Pride Community who are studying at the University of Jember class 2021-2022. The adaptation phases carried out by Solo students are the honeymoon phase, the frustration phase, the readjustment phase, and finally the resolution phase. Through adaptation phases and support from the Solo Pride Community, Solo students are able to adapt and accept differences and be well accepted by the surrounding community. Apart from that, Solo students also feel comfortable and happy because they have been able to adapt to the culture in the city of Jember. Keywords: Adaptation, Intercultural Communication, Culture Shock